Impact of nano-TiO2 on horizontal transfer of resistance genes mediated by filamentous phage transduction. Issue 4 (17th March 2020) - Han, Xue; Lv, Peng; Wang, Lu-Guang; Long, Fei; Ma, Xiao-Lin; Liu, Chang; Feng, Yu-Jie; Yang, Ming-Feng; Xiao, Xiang
Abstract : The spread of antibiotic resistance genes (ARGs) in the environment has aroused growing concern for human health and ecological safety. Abstract : The spread of antibiotic resistance genes (ARGs) in the environment has aroused growing concern for human health and ecological safety. Recent studies have confirmed that engineered nanomaterials can increase the environmental risk of ARG dissemination mediated by conjugation and transformation. However, whether nanomaterials can mediate the transductive transfer of ARGs by phage infection has not been reported. In this work, the effect of nano-TiO2 on the horizontal transfer of ARGs to E. coli TG1 through transduction by constructed phage gM13 was investigated. Our results showed that nano-TiO2 concentration, particle size, mating time and the ratio of gM13/TG1 could influence the transductive transfer of ARGs. Further studies revealed that nano-TiO2 could promote bacteriophage attachment on cell surfaces, which contributed to gM13 infection. Meanwhile, increasing membrane permeability induced by nano-TiO2 could alleviate transmembrane resistance, which facilitated the infectious entry of phage gM13 into periplasmic space. The expressions of pilus-related genes were improved when E. coli TG1 was exposed to nano-TiO2 . Thus, this work is beneficial for gaining a better understanding about the multiple environmental effects of increasingly released nanomaterials and is useful for the control of ARG dissemination in the environment.